A new species of Uropeltis Cuvier, 1829 (Serpentes: Uropeltidae) from the Anaikatty Hills of the Western Ghats of India - Jins, V.j.; Sampaio, Filipa L.; Gower, David J. (Zootaxa, 2018)
A new species of Uropeltis is described from a series of six type specimens from the Anaikatty Hills of the Western Ghats of Tamil Nadu, peninsular India. Uropeltis bhupathyi sp. nov. is distinguished from congeners by having more than 200 ventral scales, 17 dorsal scale rows at midbody and by the size and shape of the rostral and frontal shields. Although tens of specimens have been seen in the vicinity of the type locality (and previously reported as U. ellioti), the new species is known only from this locality and faces threats from road traffic, habitat loss and change, and possibly a condition that deforms heads and head shields which is at least superficially similar to snake fungal disease reported from wild snakes in North America and Europe.